Benefits of foreign language learning and bilingualism: An analysis of published empirical research 2012–2019. (7th November 2019) - Fox, Rebecca; Corretjer, Olga; Webb, Kelley
Abstract: The 21st century has seen a strong upward trajectory in empirical research on the multiple benefits that foreign language/world language learning and bilingualism can afford to both individuals and society. This analysis of research published from 2012‐2019 extends Fox et al.'s analysis of research published from 2005 to 2011 (Part I). The 100 empirical studies in Part II, drawn from seven data bases, were conducted in multiple countries. Six overarching themes emerged: cognitive abilities and benefits, aging and health, employability, academic achievement, communicative and intercultural competence, and enhanced creativity . Results report multiple cognitive benefits of language study and bi‐multilingualism, particularly later in life, including enhancement of cognitive flexibility, higher cognitive reserve in advanced age, and delay in the onset of dementia. Other results underscore the importance of early and sustained language learning and support for L1 literacy development. Additional results stress the benefits of foreign/world language skills relating to employability and academic achievement and propose that the accumulation of years of language learning positively impacts the development of cross‐cultural awareness and communicative competence. This research illustrates the importance of establishing cross‐/interdisciplinary research and sharing results with language advocates, policy makers, and legislators. The Challenge: Language educators and researchers can play a significant role in promoting the benefits of language learning and bi‐/multilingualism. How can we position the empirical research to accurately and clearly inform students and their families, school administrators, and policy makers at the local, state, and national levels to value an embrace language learning by funding and supporting language across the lifespan?